Combining Nuclear Medicine With Other Modalities: Future Prospect for Multimodality Imaging - Stephen J. Archibald PhD; Jason P. Holland PhD; Aruna Korde PhD; Andre F. Martins PhD; Adam J. Shuhendler PhD; Peter J. H. Scott PhD (Molecular Imaging)
This meeting report summarizes a consultants meeting that was held at International Atomic Energy Agency Headquarters, Vienna, in July 2022 to provide an update on the development of multimodality imaging by combining nuclear medicine imaging agents with other nonradioactive molecular probes and/or biomedical imaging techniques.